El concepto de la muerte en la obra de José María Arguedas y su relación con lo Real Maravilloso - Santa Cruz Cabrera, Reynaldo Óscar (2019)
The article examines the vision of death proposed in the work of the Peruvian writer José María Arguedas, specifically in the analysis of the story “La agonía de Rasu Ñiti” (1962), and its relationship with the approach to "lo real maravilloso". The structure of the article begs a contextualization of the concept of death from the perspective of the Latin American “real maravilloso”. Following must be a focus on the description of death in the aforementioned story. It should be noted the intention behind proposing the story in question is to demonstrate it as a representative example of the vision of death in Arguedas' narrative. Finally, it is concluded that “La agonía de Rasu Ñiti”, thanks to the perception of death that it exhibits, shows several features that approach Arguedas to “lo Real Maravilloso”.